Penerjemahan Istilah Budaya Bahasa Mandarin dalam Novel 边旅行边恋爱 (Biān lǚxíng Biān Liàn'ài) - Noor Isnaeni; Yumna Rasyid; Emzir Emzir (Jurnal Bahasa Lingua Scientia, 2018)
The purpose of this study is to obtain an overall view of culture translation and the strategies applied in translating those terms. This study used a qualitative approach using a content analysis method. The date used in this study is dialogues about culture translation and translation strategies. The researchers used Peter Newmark Theory to analyzed the culture translatoin, and used Mona Baker theory to analyzed the strategies. The results of the study showed, there are 147 data, 43 data belonged to the category of materials, 13 data belonged to the category of socials, 28 data belonged to the category of organization, tradition, activities, and religion, 51 data belonged to the category of ecology, and 12 data belonged to the category of body movements and habits. Meanwhile, there are 5 from 8 translation strategies that used by translator based on Baker theory. 43 data used translation by a more general word, 38 data used more nuetral/less expressive word, 3 data used cultural substitution, 47 data used a loan word plu explanation, and 7 data  translation by omission.